2020
DOI: 10.1136/bmjopen-2020-041511
|View full text |Cite
|
Sign up to set email alerts
|

Protocol of a retrospective, multicentre observational study on hyperthermic intrathoracic chemotherapy in Germany

Abstract: IntroductionObjective of the ‘German hyperthermic intrathoracic chemotherapy (HITOC) study’ is to evaluate the HITOC as additional treatment after surgical cytoreduction for malignant pleural tumours. Even though HITOC is applied with increasing frequency, there is no standardised therapy protocol concerning the technique of HITOC, the selection as well as dosage of chemotherapeutic agents and perioperative management in order to provide a safe and comparable, standardised treatment regime.Methods and analysis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 29 publications
(33 reference statements)
0
16
0
Order By: Relevance
“…The approval of the ethics committee of the University of Regensburg (reference number: 18-1119-104) and of the ethics committees of the participating centres was obtained. The study protocol was developed and published before collecting and analyzing the data [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The approval of the ethics committee of the University of Regensburg (reference number: 18-1119-104) and of the ethics committees of the participating centres was obtained. The study protocol was developed and published before collecting and analyzing the data [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…The study protocol specified the following inclusion criteria: malignant pleural tumours and HITOC after CRS in one surgery. Conversely, treatment without HITOC and HITOC without CRS (not following consensus-based recommendations) were exclusion criteria [ 14 ]. The choice of chemotherapeutic agents (alone or in combination) and also the dosage of chemotherapeutic agents for the intracavitary administration was determined by each hospital according to its own experience and protocols independently of clinical conditions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, a retrospective, multi-center observational study, which is funded by the German Research Foundation analyses approximately 350 patients who underwent surgical cytoreduction combined with subsequent HITHOC in four German University Hospitals (46). The results of this retrospective, multi-center study should allow a better standardization of the HITHOC-procedure including D with or without HITHOC.…”
Section: Future Studiesmentioning
confidence: 99%
“…The HITHOC acts with a double action: chemotherapeutic drug has a local and direct effect on the tumor cells while hyperthermia enhances the impact of chemotherapy by increasing its penetration into the tissue (13). Furthermore, although many experiences and studies have been reported to date, there is no standardized protocol for HITHOC (14)(15)(16).…”
mentioning
confidence: 99%